DWI lesion patterns in cancer-related stroke: specifying the phenotype - Schwarzbach, Christopher Jan; Fatar, Marc; Eisele, Philipp; Ebert, Anne; Hennerici, Michael G.; Szabo, Kristina (Cerebrovascular diseases. Extra, 2015)
Background: Due to the lack of specific diagnostic markers, the diagnosis of cancer-related stroke strongly depends on its phenotype. Distinct DWI lesion patterns with involvement of multiple vascular territories have been reported repeatedly in cancer-related stroke but have not been addressed in detail in a selected cohort of prospectively recruited cancer patients with emphasis on hypercoagulable conditions. Patients and Methods: Ischemic stroke patients with known malignant cancer activity, laboratory evidence of strong plasmatic hypercoagulation (D-dimer levels >3 µg/ml) and without competing stroke etiologies according to the recently introduced ASCOD (A - atherosclerosis, S - small vessel disease, C - cardiac pathology, O - other cause, and D - dissection) classification of evidence-rated etiology of stroke subtypes were included in the analysis. Cerebral MRI on admission was reviewed with respect to ischemic lesion patterns. Results: Thirty-two patients met the inclusion criteria. The mean D-dimer levels were 15.39 µg/ml (±10.84). Acute infarction in ≥2 vascular territories was present in 27/32 (84%) patients. (Micro-) embolic scattering of infarction was present in 25/32 (78%) patients. Evidence for previous, potentially oligosymptomatic infarction was found in 16 (50%) patients, demonstrated by the additional presence of subacute or chronic ischemic lesions. Conclusion: When excluding competing embolic and nonembolic stroke etiologies, the pattern of scattered DWI lesions in multiple vascular supply territories strongly dominates the phenotype of cancer-related stroke. Additionally, evidence of recurrent infarction is frequent in this cohort of patients. This is not only important for the diagnosis of cancer-related stroke itself but may prove helpful for the identification of cancer-related stroke patients with unknown malignancy at the time of stroke manifestation and evaluation of strategies for secondary prevention.